A new species of Takydromus (Squamata: Lacertidae) from northeast India - Chettri, Basundhara; Mothey, Rabina; Ghatani, Sudeep; Deepak, V.; Rai, Ananta (Zootaxa, 2026)
The diversity of lizards in the northeast Indian biodiversity hotspot is underestimated, as evidenced by many new species recorded in recent years. Here, we describe a new species of Takydromus from Ultapani, Kokrajhar District, Assam, India. This newly identified species is distinguished from its relatives in its distinctive morphological features and significant genetic variation in the mitochondrial 12S rRNA and COI genes. We have also added the missing molecular data for T. sikkimensis and T. khasiensis. In the light of these new data, we discuss the phylogenetic relationships of Takydromus species from the Indian subcontinent with their congeners.